1984
DOI: 10.1042/bj2180953
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase inhibitors in rat serum. Purification and partial characterization of three functionally distinct trypsin inhibitors

Abstract: Three different serine proteinase inhibitors were isolated from rat serum and purified to apparent homogeneity. One of the inhibitors appears to be homologous to a1-proteinase inhibitor isolated from man and other species, but the other two, designated rat proteinase inhibitor I and rat proteinase inhibitor II, seem to have no human counterpart. ac-Proteinase inhibitor (Mr 55000) inhibits trypsin, chymotrypsin and elastase, the three serine proteinases tested. Rat proteinase inhibitor I (M' 66000) is active to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, α 1 -PI has also been described as being of importance in modulating immunity, inflammation, proteostasis, apoptosis, and possibly cellular senescence (Hunt and Tuder, 2012). Alpha 1 -proteinase inhibitor has been purified from many species including human (Pannell et al, 1974), dog (Melgarejo et al, 1996), cat (Fetz et al, 2004), sheep (Mistry et al, 1991), goat (Vankan and Bell, 1993), rabbit (Koj et al, 1978a), mouse (Minnich et al, 1984), rat (Kuehn et al, 1984), guinea pig (Suzuki et al, 1990), Rhesus monkey (Berninger and Mathis, 1976), and opossum (Catanese and Kress, 1993). Across species, the protein structure and function remain similar, however, a relative deficiency has been reported in people with certain genetic genotypes (Brebner and Stockley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, α 1 -PI has also been described as being of importance in modulating immunity, inflammation, proteostasis, apoptosis, and possibly cellular senescence (Hunt and Tuder, 2012). Alpha 1 -proteinase inhibitor has been purified from many species including human (Pannell et al, 1974), dog (Melgarejo et al, 1996), cat (Fetz et al, 2004), sheep (Mistry et al, 1991), goat (Vankan and Bell, 1993), rabbit (Koj et al, 1978a), mouse (Minnich et al, 1984), rat (Kuehn et al, 1984), guinea pig (Suzuki et al, 1990), Rhesus monkey (Berninger and Mathis, 1976), and opossum (Catanese and Kress, 1993). Across species, the protein structure and function remain similar, however, a relative deficiency has been reported in people with certain genetic genotypes (Brebner and Stockley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Sinha et al [6] used bovine trypsin, which is susceptible to inhibition by other plasma proteinase inhibitors such as a2-antiplasmin and antithrombin III, and alPI is not the most likely inhibitor [28]. Furthermore, mammalian sera, including human [29], goat [11], horse [30], rabbit [10], rat [7] and mouse [8], have been reported to contain more than one proteinase inhibitor in the z1-globulin fraction, which can be separated by PAGE. Of particular relevance to this work are the studies where two of these inhibitors have been partially characterized [7,8,29,31] and which differ in their Mr and their inhibitory capacities towards elastase and bovine trypsin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mammalian sera, including human [29], goat [11], horse [30], rabbit [10], rat [7] and mouse [8], have been reported to contain more than one proteinase inhibitor in the z1-globulin fraction, which can be separated by PAGE. Of particular relevance to this work are the studies where two of these inhibitors have been partially characterized [7,8,29,31] and which differ in their Mr and their inhibitory capacities towards elastase and bovine trypsin. In each case the proteinase inhibitor with the lower Mr (53 000-58 000) behaved like human aclPI and inhibited both elastase (leucocyte or pancreatic) and bovine trypsin at a molar ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11) Some properties of the Cil-proteinase inhibitor, for example, pH-stability,38) thermo-stability,39) isoelectric point,32.33) inhibitory spectrum, 35.36,40) and stability of E· I complex against denaturing and reducing reagents such as SDS and 2-mercaptoethanol,35 "'37,41) were very similar to those of our inhibitor. Recently, Kuehn et al 42 ) reported that rat serum contains a number of serine proteinase inhibitors such as Ci 1 -proteinase inhibitor and rat proteinase inhibitors I-I and I-II. Subsequently, they also found these serine proteinase inhibitors in rat skeletal muscle by immunological methods.…”
Section: Gel Electrophoretic Analysis Oj' the Reaction Oj' The Inhibmentioning
confidence: 99%